(untitled) (Al-Qamar, 2019)
This paper examines the process and progress in the traditional irrigation activity better known as Chairbandī that was a prominent feature in the canal irrigated areas of Punjab and Sindh plains. The old native irrigation in the Muslim State of Bahawalpur was based on Chairbandī or collective labour under community management. This system also supposed to be a bond of unity among the village communities of a Muslim society. The paper investigates the pattern, and pros and cons of Chairbandī institution and how it gradually converted into the modern and calculated water management system particularly, under the British Agency. The study of such historical paradigms of a Muslim polity is certainly a contribution to the rich heritage of Pakistan.